Optimism for the Future in Younger and Older Adults. (9th January 2018) - Durbin, Kelly A; Barber, Sarah J; Brown, Maddalena; Mather, Mara
Abstract: Objectives: Research has suggested that older adults are less optimistic about their future than younger adults; however, a limitation of prior studies is that younger and older adults were forecasting to different ages and stages of life. To address this, we investigated whether there are age differences in future optimism when people project to the exact same age. We also tested whether optimism differs when projecting one's own future versus another person's future. Method: Participants were 285 younger and 292 older adults recruited from Amazon Mechanical Turk. Participants completed writing and word-rating tasks in which they imagined their own future in 15 years, their own future at age 85, or the average person's future at age 85. Results: Younger adults were more optimistic than older adults about their own future in 15 years. In contrast, both age groups were similarly optimistic about their future at age 85 and expected it to be more positive than others' future at age 85. Discussion: Contrary to previous research, younger and older adults had comparable future forecasts when projecting to the exact same age. These findings emphasize the need to consider age and stage of life when examining age differences in future optimism.